2006
DOI: 10.1063/1.2204633
|View full text |Cite
|
Sign up to set email alerts
|

The swimming of animalcules

Abstract: Animalcules can swim in a viscous fluid at low Reynolds number and low Stokes number by moving their body parts in a periodic coherent fashion. The swimming motion is analyzed in a simple model of beads subject to periodic one-body forces. In the model the animalcule is held together by reactive two-body forces. The nonlinear equations of Stokesian dynamics are formulated on the basis of the Oseen tensor. Under suitable conditions the solution of the equations of motion has a limit cycle character. The limit c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
96
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 17 publications
9
96
0
Order By: Relevance
“…Recently, Leshansky et al [17] have considered the remarkably efficient locomotion of an elongated treadmilling body, which can propel itself at nearly the same velocity of the surface motion. Other simple means of propulsion proposed for locomotion at zero Reynolds number include a deformable two-dimensional loop [18], systems of two [19,20], three [21,22] or N spheres [23], flapping near deformable interfaces [24], a rehinging swimmer [25], and a jellyfish-inspired bilayer vesicle [26]. For a more complete list of references we refer the reader to Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Leshansky et al [17] have considered the remarkably efficient locomotion of an elongated treadmilling body, which can propel itself at nearly the same velocity of the surface motion. Other simple means of propulsion proposed for locomotion at zero Reynolds number include a deformable two-dimensional loop [18], systems of two [19,20], three [21,22] or N spheres [23], flapping near deformable interfaces [24], a rehinging swimmer [25], and a jellyfish-inspired bilayer vesicle [26]. For a more complete list of references we refer the reader to Ref.…”
Section: Introductionmentioning
confidence: 99%
“…(2.2) the nature of the forces {F j } need not be specified. In an earlier calculation [12] we have considered microswimmers with internal harmonic interactions, driven by actuating forces. The forces are of the form…”
Section: Harmonic Interactions and Actuating Forcesmentioning
confidence: 99%
“…Numerical calculations have shown that the equations of Stokesian dynamics for a set of spheres lead to numerical instability of the solution, unless the spheres are subject to attractive direct interactions keeping them together [12]. For simplicity one can assume harmonic elastic interactions between the spheres, bound harmonically to sites on a given equilibrium structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model with three linked spheres, presented by Najafi and Golestanian [7], has three spheres connected via two deformable rods(see also [8]). Examples of propulsion motion, characteristic for bacterial motions and involving cilia waves or rotation of flagella, have been considered [9][10][11][12][13][14][15][16][17].…”
mentioning
confidence: 99%